Quality schooling : a pragmatic approach to some current problems, topics and issues - Aspin, David N. (Cassell, 1994)
The concept of quality and the provision of quality schooling. The relationship between theory, research, policy and practice. The quality debate. The search for quality. Restructuring education in the interests of quality. Redefining the curriculum. Democratic values and the Democratic school...